The Impact of Language Skills on Immigrants’ Labor Market Integration: A Brief Revision With a New Approach - Schuß, Eric [Verfasser] (My University, 2018)
"I examine the impact of language skills on immigrants' labor market performance by applying a new approach, which allows to estimate wage benefits attributed to initial language skills at arrival. By exploiting unique data, I isolate the endogenous part of current German skills and instrument current command by German proficiency measured retrospectively at the point in time of migration. This approach tackles the problem that labor market effects from current language skills are at risk to reflect merely the sum of a successful residence in Germany and only display growth effects. I find that a good command of German increases labor market income by 47.0% for males, while no significant language effects are detected for females. Further analyses illustrate that differences in language effects by gender can be attributed to selection into different occupations and part-time employments and that language operates complementary and enables cross-border transferability of human capital." (author's abstract; BIBB-Doku)
Keywords: P 1.5 Migranten; Einwanderer; Berufliche Integration; Sprachkenntnisse; Einflussfaktor